The Exploration of Causal Conjunctions in Colleen Hooversâ€™ â€œNovember 9â€ Novel - Ni Putu Riandhani; Putu Nur Ayomi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
Conjunctions are crucial cohesive devices that help establish connections between propositions. It is an integral part of language use, especially in literature. One prominent use of conjunctions in conveying narrative relationships can be seen in the Novel, â€œNovember 9â€, by Colleen Hoover. This study focuses on causal conjunctions and investigates the types and functions of causal conjunctions in the novel â€œNovember 9.â€ The research employs a library research and qualitative methodology to explore the existing pieces of literature comprehensively. The analysis identifies four distinct causal conjunctions within the Novel. â€œsoâ€ signifies general causal relations, establishing cause-and-effect links between actions or events. It also introduces specific causal relations, elucidating consequences following a preceding statement. â€œthenâ€ represents conditional relations, altering the polarity between positive and negative statements. â€œbecauseâ€ conveys general respective relations, offering reasons for prior statements. Each causal conjunction uniquely conveys cause-and-effect relationships, consequences, explanations, and reasons throughout the narrative. The study enriches the understanding of causality and conjunctions in literature, shedding light on how they shape logical and cogent sentences. This study is a valuable resource for academics exploring the intricate relationship between causality and conjunctions in â€œNovember 9.â€ By unveiling the nuanced functions of causal conjunctions, it encourages further research into broader implications of conjunction usage in literary works. Ultimately, it underscores the significance of conjunctions in crafting coherent and impactful narratives.